(untitled) (Journal of the College of Basic Education, 2022)
In view of the rapid development that the world is witnessing in various fields of life, such as social, economic, cultural and artistic life, and since reduction is a technical act based on the disposal and deletion of everything that would not affect the form and not transform it into another form that changes the meaning of the form semantically, and abstraction is access to the essence Objects (form), i.e. getting rid of all that is mimicking natural forms and reaching their latent meaning.